2016
DOI: 10.1021/acs.orglett.6b03497
|View full text |Cite
|
Sign up to set email alerts
|

Relay Visible-Light Photoredox Catalysis: Synthesis of Pyrazole Derivatives via Formal [4 + 1] Annulation and Aromatization

Abstract: A relay visible-light photoredox catalysis strategy has been accomplished. Three successive photoredox cycles (one oxidative quenching cycle and two reductive quenching cycles) are engaged in a single reaction with one photocatalyst. This strategy enables formal [4 + 1] annulation of hydrazones with 2-bromo-1,3-dicarbonyl compounds, which functionalizes three C-H bonds of hydrazones. This method affords rapid access to a complex and biologically important pyrazole scaffold in a step-economical manner with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…The rational combination of photocatalytic SET oxidation and reduction could also provide a promising approach for developing new cascade reactions. In contrast to their previous study on the photocatalytic cascade alkylation of C(sp 2 )−H and C(sp 3 )−H bonds of aldehyde hydrazones with 2,2‐dibromo‐1,3‐dicarbonyls, the groups of Zhu and Yu jointly revealed that the reaction of aromatic‐aldehyde‐derived N ‐tetrahydroisoquinoline hydrazones 43 and diethyl 2‐bromo‐1,3‐dicarbonyl compounds 44 could undergo three successive photoredox cycles to give the corresponding complex and biologically important fused pyrazoles 45 in good yields (Scheme ) . Specifically, in this process, one SET reduction and two SET oxidations are situated together to sequentially activate the 2‐bromo‐1,3‐dicarbonyl compounds 44 and the key intermediates, hydrazone 43‐A and dihydropyrazole 43‐C .…”
Section: Photocascade Catalysis Involving Single‐electron‐transfer Omentioning
confidence: 69%
See 1 more Smart Citation
“…The rational combination of photocatalytic SET oxidation and reduction could also provide a promising approach for developing new cascade reactions. In contrast to their previous study on the photocatalytic cascade alkylation of C(sp 2 )−H and C(sp 3 )−H bonds of aldehyde hydrazones with 2,2‐dibromo‐1,3‐dicarbonyls, the groups of Zhu and Yu jointly revealed that the reaction of aromatic‐aldehyde‐derived N ‐tetrahydroisoquinoline hydrazones 43 and diethyl 2‐bromo‐1,3‐dicarbonyl compounds 44 could undergo three successive photoredox cycles to give the corresponding complex and biologically important fused pyrazoles 45 in good yields (Scheme ) . Specifically, in this process, one SET reduction and two SET oxidations are situated together to sequentially activate the 2‐bromo‐1,3‐dicarbonyl compounds 44 and the key intermediates, hydrazone 43‐A and dihydropyrazole 43‐C .…”
Section: Photocascade Catalysis Involving Single‐electron‐transfer Omentioning
confidence: 69%
“… Visible‐light‐induced photocatalytic cascade reaction of hydrazones and 2‐bromo‐1,3‐dicarbonyl compounds …”
Section: Photocascade Catalysis Involving Single‐electron‐transfer Omentioning
confidence: 99%
“…Three successive photoredox cycles (one oxidative cycle and two reductive quenching cycles) were engaged in a reaction with one photocatalyst. Multiple quenching cycles could be demonstrated in a single reaction involving formal 4+1 annulation of hydrazone with 2-bromo diethylmalonate [23] (Figure 30).…”
Section: Relay Visible-light Photocatalysismentioning
confidence: 99%
“…Later on, the same group also investigated the reactivity of the monohalogenated diethyl 2‐bromomalonate ( 41 ) under similar reaction conditions . Remarkably, reactions between 41 and a range of N ‐benzyl‐derived hydrazones in the presence of fac ‐[Ir(ppy) 2 dtbbpy](PF 6 ) (dtbbpy = 4,4′‐di‐ tert ‐butyl‐2,2′‐bipyridine) as photocatalyst also yielded nitrogen heterocyclic compounds, in the form of 4‐functionalized pyrazole derivatives 42 , one of the ester groups having been lost (Scheme a).…”
Section: Carbon–carbon Bond Formationmentioning
confidence: 99%